Noninvasive Techniques Provide Novel Insights for the Elusive Bush Dog (Speothos venaticus) - Dematteo, Karen (2014)
The bush dog (Speothos venaticus), a small and rarely seen canid from Central and South America, has proven extremely challenging to locate and study in the wild, making the development of species-specific and comprehensive carnivore conservation strategies difficult. From May to August 2011, a detection-dog-handler team located 34 scats from bush dogs in the northern (n = 26) and central (n = 8) zones of Misiones, Argentina. We identified 22 unique genotypes (14 northern and 8 central) and assigned sex to 100% of the genotyped scats. Only half of the scats were located inside 7 protected areas (4 northern and 3 central); the remaining half were located in 4 sites outside of protected areas (3 northern and 1 central). Results suggest low but significant differentiation between zones for bush dogs (FST = 0.049, P = 0.010). Bush dogs demonstrated high habitat-use flexibility and a close association with altered habitat; however, altered habitat may not be optimal for the species because of the potential for lower prey densities and risk of exposure to life threatening diseases by domestic dogs. The effectiveness of noninvasive techniques (detection dogs, genetic analyses of scat, Geographic Information System technology) in studying the ecology of bush dogs not only opens the door for additional studies of a species that has proven difficult to study with standard survey techniques, but also provides an alternative approach that conservationists can use independent of habitat type and presence of humans.